Tensile Properties and Fracture Reliability of Melt-extracted Gd-rich Amorphous Wires - Shen,Hongxian (2015)
Gd60Al20Co20 amorphous wires with smooth surfaces and circular cross-sections were fabricated by a melt-extraction technique. The mechanical properties of the extracted microwires were evaluated by tensile tests and their fracture reliability was estimated by using Lognormal and two- or three- parameter Weibull analysis, respectively. The microwires exhibit a tensile fracture strength ranging from ~788 to ~1196 MPa, with a mean value of 1008 MPa and a standard variance of 121 MPa. Lognormal method of statistical analysis presents that the average stress of microwires is ~1012 MPa. Weibull statistical analysis indicates that the two-parameter tensile Weibull modulus is 8.5 and the three-parameter Weibull modulus is 5.3 with a threshold value ~365 MPa for as-extracted amorphous microwires. Our results show that the extracted Gd-based wires possess excellent tensile properties and high fracture reliability, with a high potential for applications in and magnetic refrigeration.